Price Discovery and Trading After Hours - Barclay, Michael J.; Hendershott, Terrence (Review of Financial Studies, 2003)
We examine the effects of trading after hours on the amount and timing of price discovery over the 24-hour day. A high volume of liquidity trade facilitates price discovery. Thus prices are more efficient and more information is revealed per hour during the trading day than after hours. However, the low trading volume after hours generates significant, albeit inefficient, price discovery. Individual trades contain more information after hours than during the day. Because information asymmetry declines over the day, price changes are larger, reflect more private information, and are less noisy before the open than after the close.